PKM Kewirausahaan Pembuatan Keripik Pisang Rasa (KRISANGRA) - Mustari; Nurjannah; Nur Arisah; Ratnah S; Nahriana (CV. ALIM'SPUBLISHING, 2024)
One activity that can increase the entrepreneurial spirit of the community is a home industry business or what is usually called a home business in making Banana Flavored Chips (KRISANGRA). Processing of higher quality banana chip products and a more contemporary design. As globalization progresses, society will be able to provide the ever-increasing need for nutritious food that everyone needs to be healthy. An opportunity for the general public to start a simple food or snack business with many banana-based preparations. With innovation and increasingly developing times, these banana chips are prepared with various flavors like the ones we make, especially balado, chocolate and cheese milk, suitable as snacking companions. Various flavors of banana chips are one of the snack products that is most popular with consumers in various circles. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained were (1) Training on making Flavored Banana Chips (KRISANGRA) was responded well by participants; (2) The high interest and motivation of the training participants really supports the transfer of knowledge and skills from the service to the training participants, so that the training material provided can be absorbed by all; and (3) The training product for making Flavored Banana Chips (KRISANGRA) can be consumed daily and can be used as an entrepreneurial product